1980
DOI: 10.1111/j.1365-2125.1980.tb01828.x
|View full text |Cite
|
Sign up to set email alerts
|

Abuse and paradoxical effects of analgesic drug mixtures.

Abstract: 1 In patients with chronic pain, two types of analgesic drug dependence occur, that is, dependence of the barbiturate‐type and of the morphine‐ type. Eighty cases of analgesic drug dependence of the barbiturate‐type were examined. All these patients were dependent on drug combinations, not a single patient being on one analgesic alone. 2 Psychotropic agents were found to be the common pharmacological denominator of all abused preparations. These findings confirm the hypothesis that the addition of psychotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The first ergotamine withdrawal protocols were proposed independently by Graham, Friedman and Lippmann in 1955 [ 3 , 6 – 8 ]. In the 1970s, multiple authors wrote on the association between overuse of mixed analgesics, including those based on ergotamine, barbiturates and codeine, and headache progression [ 11 , 12 ]. In 1982, Mathew et al outlined that overuse of analgesics contributed to the transformation of episodic migraine (EM) into daily headaches and a few years later the same group introduced the term “transformed or evolutive migraine” to describe the entity [ 3 , 13 , 14 ].…”
Section: Moh In Historical Perspectivementioning
confidence: 99%
“…The first ergotamine withdrawal protocols were proposed independently by Graham, Friedman and Lippmann in 1955 [ 3 , 6 – 8 ]. In the 1970s, multiple authors wrote on the association between overuse of mixed analgesics, including those based on ergotamine, barbiturates and codeine, and headache progression [ 11 , 12 ]. In 1982, Mathew et al outlined that overuse of analgesics contributed to the transformation of episodic migraine (EM) into daily headaches and a few years later the same group introduced the term “transformed or evolutive migraine” to describe the entity [ 3 , 13 , 14 ].…”
Section: Moh In Historical Perspectivementioning
confidence: 99%
“…Despite this success, there is little time to rest on our laurels, as there remains a need to generate a greater understanding of all anti-migraine therapies, to include their clinical mechanisms of action and their potential unwanted side effects/risk factors. Unfortunately, a common theme has emerged for several drugs including triptans, ergotamine, caffeine, paracetamol (acetaminophen) and opioids (13), whereby their excessive use leads to an increased risk of increasing migraine frequency and the development of a chronic state termed medication overuse headache (MOH) (4). Importantly, MOH appears a particular characteristic of headache disorders, with people who have a personal or family history of headaches most vulnerable, suggesting a potential genetic component (5).…”
mentioning
confidence: 99%
“…In fact, there are some evidence that reduction in analgesic usage can produce reduction in headache activity. [21][22][23] In the present study, it was found that reductions in migraine were highly correlated with reductions in medication. Furthermore, reductions in medication were larger in the classical migraine group than in the common migraine condition.…”
Section: Discussionmentioning
confidence: 66%
“…Because reductions in analgesic medication have been found to relieve rebound pain effects in headache, [21][22][23] Because all of the significant correlations were positive, those analyses indicate that the larger reductions in migraine were more likely to be found in patients who had achieved the largest reductions It will be noted that comparisons between classical and common migraine patients on the basis of the levels of physiological control achieved during biofeedback training were not made. Neither were the physiological data analyzed to determine the amount of self-regulation-skills achieved in each condition.…”
Section: Examination Ofmentioning
confidence: 99%